Do the project manager's soft skills matter? Impacts of the project manager's emotional intelligence, trustworthiness, and job satisfaction on project success - Marcela Castro; André Barcaui; Bouchaib Bahli; Ronnie Figueiredo (Administrative Sciences, 2022)
Recent warnings have been raised about the project success rate in organizations. Among many reasons of disappointing results, research on project management reveals a gap in examining project success. Traditionally, project success has been widely studied from the rational view but rarely from the behavioral view. Today's businesses are facing multiple challenges and opportunities in a volatile market environment that require constant changes within organizations and leaders' behavior. The role of project managers is no longer the same. This study attempts to update the discussion of project managers soft skills by examining two major behavioral factors: project manager's emotional intelligence and trustworthiness and their impact on job satisfaction and project success. This research compiles a quantitative survey. Data were collected from 101 project team professionals. The results reveal that project managers' emotional intelligence and their team members' trust in them impact project success significantly. The findings provide organizations with a necessary complementary behavioral view of project management. Organizations can take project manager trustworthiness and emotional intelligence into account when recruiting and training project managers and throughout the project planning and execution life span.
Keywords: 350; emotional intelligence; empirical study; job satisfaction; project management; project success; trust